Countering cognitive biases in minimising low value care. Issue 9 (15th May 2017) - Scott, Ian A; Soon, Jason; Elshaug, Adam G; Lindner, Robyn
Summary: Cognitive biases in decision making may make it difficult for clinicians to reconcile evidence of overuse with highly ingrained prior beliefs and intuition. Such biases can predispose clinicians towards low value care and may limit the impact of recently launched campaigns aimed at reducing such care. Commonly encountered biases comprise commission bias, illusion of control, impact bias, availability bias, ambiguity bias, extrapolation bias, endowment effects, sunken cost bias and groupthink. Various strategies may be used to counter such biases, including cognitive huddles, narratives of patient harm, value considerations in clinical assessments, defining acceptable levels of risk of adverse outcomes, substitution, reflective practice and role modelling, normalisation of deviance, nudge techniques and shared decision making. These debiasing strategies have considerable face validity and, for some, effectiveness in reducing low value care has been shown in randomised trials.